Applications of molecular fossils in lacustrinestratigraphy - Wang, Guangli; Li, S.; Wang, T.; Zhang, L. (Kexue Chubanshe, 2010)
Biomarkers, or the so-called molecular fossils, are used tentatively in the Eogene lacustrine stratigraphy study in the Jiyang Sub-basin. Notwithstanding the fact that unidentified microfossils or amorphism and acritarchae are widely distributed in lacustrine source rocks, molecular fossils are useful to identify the sources. It is helpful to reconstruct the palaeo-enviroment, palaeo-ecosystem and compartmentalize the stratigraphic sequence by using molecular fossils with which the existence and types of microbes including bacteria, archaea and certain algae can be identified.